1505 EASiE: ENT and Airway Simulation in Emergencies. (12th October 2021) - Gurung, P; Luff, E; Waters, C; Castelhano, R
Abstract: Aim: A literature review of undergraduate ENT teaching found that most final year medical students and junior doctors did not feel adequately prepared for clinical practice in ENT. Other surveys found junior doctors lack confidence in recognising or initiating management in patients with blocked tracheostomies. To improve this, we ran a simulation session designed to replicate airway emergencies that junior doctors should be able to manage. The aim was to improve confidence in and knowledge of basic management of airway emergencies, including tracheostomies. Method: Groups of 4-6 final year medical students participated in 3 scenarios: 2 tracheostomy-related and 1 partially compromised airway. The students had attended a session introducing tracheostomies and the algorithms produced by the National Tracheostomy Safety Project for tracheostomy emergencies. A semi-structured debrief followed each scenario, highlighting key learning points. The students completed a pre- and post-session questionnaire, rating confidence in several domains related to the scenarios. Results: Of 24 participants, the percentage of students who felt confident or very confident in the following domains were compared pre- and post-simulation respectively: recognising a potential airway problem (0% vs 71%); identifying an altered airway (0% vs 75%); managing a potentially compromised surgical airway (4% vs 71%); initially managing a compromised airway (8% vs 67%); and identifying when to escalate with a potential airway problem (25% vs 96%). Conclusions: Simulation is a valuable tool that can be used to improve both knowledge and confidence in managing potential airway problems in final year medical students. This supports findings from other studies.